Use of Saliva in Diagnosis of Periodontitis: Cumulative Use of Bacterial and Host-Derived Biomarkers - Ulvi Kahraman Gursoy (Frontiers Research Topics, 2017)
Periodontitis is an infection-induced inflammatory disease of the tooth supporting tissues. Treatment of periodontal diseases and regeneration of the effected tissues can be possible only in the early diagnosis of the disease. If left undiagnosed or untreated, periodontitis leads to irreversible soft and hard tissue destruction and finally to tooth loss. Saliva is known to contain inflammatory mediators, host tissue and cell degradation products as well as microbial metabolites and enzymes, reflecting the health status of the oral cavity. In this topic, in collaboration with the well-known scientists working on the field of salivary diagnostics, we demonstrate evidence on monitoring periodontitis by salivary analysis.